FRAMING DEVICE IN GAMSON AND MODIGLIANI MODEL ABOUT THE NEWS OF KOMISI PEMBERANTASAN KORUPSI - Febriana, Ratih Putri; Sukarelawati, Sukarelawati; Fitriah, Maria (JURNAL KOMUNIKATIO, 2020)
Firli Bahuriâ€™s election as chairman of Komisi Pemberantasan Korupsi, and efforts to revise the laws of anti-corruption Commission triggered the noise, the media have a responsibility to tell it. Each media has constructed the news of KPK withÂ  differently. The problem in this study is "How does the framing device in Gamson and Modigliani model about the news of Komisi Pemberantasan Korupsi on the headline of Tempo Magazine 4524/16-22 September, 2019 edition?". This study aims to know the framing device in Gamson and Modigliani model about the news of Komisi Pemberantasan Korupsi on the headline of Tempo Magazine 4524/16-22 September, 2019 edition. The study uses a qualitative approach with constructionist paradigm, the method this study uses framing analysis of Gamson and Modigliani, the primary data obtained by documentation techniques and secondary data obtained from the library research. The results showed, Tempo used the framing device for contructed the bad news model. â€œHidup-Mati Komisi Antikorupsiâ€ and â€œJendral Polisi Sarat Kontroversiâ€ articles have fulfilled all the elements in the framing device, but â€œBatal Istana Koreksi Hasil Seleksiâ€ article does not fulfilled one of of the elements, that isÂ  metaphors.